Remittances and its impact on the Kerala Economy and Society - S Irudaya Rajan K.C. Zachariah (Institute of Social Studies, 2007)
The basic data used in the present paper was primary information collected from 10,000 households from 225 localities selected at random from all the 14 districts of Kerala in 2003. According to this survey, the number of emigrants from Kerala was 18.4 lakh or 27 emigrants per 100 households. Women accounted for 16.8 per cent. Gulf countries are the principal destinations of Kerala emigrants with 91 per cent. In 2003, India has passed a milestone in the matter of workers remittances. With $23.0 billion in Remittances, Indian Diaspora top in worker remittances, ahead of other major countries in this matter such as Mexico and the Philippines (World Bank, 2005). According to the estimates of the World Bank, the remittances have grown steadily from $ 0.08 million in 1970, to $ 2.8 billion in 1980, $ 3.4 billion in 1991, about $ 11.7 billion in 2000 and $ 23 billion in 2004. Non-resident Indian remittances were more than double the Foreign Direct Investments (FDI) investments of $8.2 billion during the year 2003-2004. (The Hindu, 2004). Our estimates indicated that the total remittance to Kerala in 2004 were in the vicinity of Rs. 18.5 thousand crores. It has both macro and micro implications. The net state domestic product (NSDP) for Kerala is reported to be Rs 83,782 crore for 2003. The remittances account about 22 per cent of the NSDP. The importance of Remittances to Kerala's economy is evident from a few other comparisons. Remittances were 1.74 times the revenue receipts of the state, 7 times of the transfers to the state from the Central Government and 1.8 times the annual expenditure of the Kerala Government. Remittances were sufficient to wipe out 60 per cent of the Kerala state's debt. The remittances in 2003 were 15 times of the export earnings from cashew and 18 times of those from marine products. At the household level, it has contributed to investments in education and health, accumulation both moveable and non-moveable assets